2022
DOI: 10.3390/foods11162503
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Health Risk Assessment for Exposure to Aluminum from Infant Formulas and Children under the Age of Five’s Food Products among Arab Infants: Experience from Lebanon

Abstract: Chronic dietary aluminum (Al) exposure can have various negative effects on health. The aim of our study is to (1) assess the contamination level of Al in infant formulas (n = 41) and baby food products (n = 76) available in the Lebanese market, and to (2) evaluate the margin of exposure of Al through the consumption of these foods among children under the age of five in Lebanon. Flame atomic absorption spectrometry (FAAS) was used to evaluate all of the samples. Al levels in all tested children’s food items w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, the European Food Safety Authority (EFSA) has set a TWI (Tolerable Weekly Intake) of 1 mg/kg bw for Al in all food sources [58]. The Committee observed that the PTWI may be exceeded in some demographics, particularly in children who regularly consume foods containing Al-based additives or ingredients [59]. When the EWI values given in Table 4 were compared with the PTWI value, it was observed that all infant formulas were below the limit value.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the European Food Safety Authority (EFSA) has set a TWI (Tolerable Weekly Intake) of 1 mg/kg bw for Al in all food sources [58]. The Committee observed that the PTWI may be exceeded in some demographics, particularly in children who regularly consume foods containing Al-based additives or ingredients [59]. When the EWI values given in Table 4 were compared with the PTWI value, it was observed that all infant formulas were below the limit value.…”
Section: Resultsmentioning
confidence: 99%
“…The AlCl 3 doses, in male and female laboratory rodents, usually diluted in drinking water, can vary from 0.4 to more than 4000 mg/kg. In this study, we chose to use a relatively low dose of Al, as it is closer to the tolerable intake recommended by the International Scientific Committee of Experts on Addictive Foods (Ibrahim et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this metal is also found in packaging, antacids, vaccines, antiperspirants, kidney dialysis, parenteral nutrition, and cosmetics (Darbre et al, 2011; de Oliveira et al, 2010; El‐Sayed et al, 2011; Shaw et al, 2013). According to the International Scientific Committee of Experts on Addictive Foods (JECFA), it has been determined that the tolerable intake of Al corresponds to 2 mg/kg/week (Crisponi et al, 2013; Ibrahim et al, 2022). However, the daily intake of foods containing Al additives can reach 100 mg/day (Saiyed & Yokel, 2005).…”
Section: Introductionmentioning
confidence: 99%